A Ratiometric Fluorescence Amplification Using Copper Nanoclusters with o-Phenylenediamine Sensor for Determination of Mercury (II) in Natural Water - Ampika Phoungsiri; Natee Lerdpiriyaskulkij; Pathavuth Monvisade; Ekarat Detsri; Arjnarong Mathaweesansurn (Sensors, 2023)
A simple and rapid method for determining mercury (II) has been developed using L-cysteine-capped copper nanocluster (CuNCs) with o-phenylenediamine (OPD) as the sensor. The characteristic fluorescence peak of the synthesized CuNCs was observed at 460 nm. The fluorescence properties of CuNCs were strongly influenced by the addition of mercury (II). Upon addition, CuNCs were oxidized to form Cu2+. Then, the OPD were rapidly oxidized by Cu2+ to form o-phenylenediamine oxide (oxOPD), as evidenced by the strong fluorescence peak at 547 nm, resulting in a decrease in the fluorescence intensity at 460 nm and an increase in the fluorescence intensity at 547 nm. Under optimal conditions, a calibration curve between the fluorescence ratio (I547/I460) and mercury (II) concentration was constructed with a linearity of 0–1000 µg L−1. The limit of detection (LOD) and limit of quantification (LOQ) were found at 18.0 µg L−1 and 62.0 µg L−1, respectively. The recovery percentage was in the range of 96.8–106.4%. The developed method was also compared with the standard ICP-OES method. The results were found to be not significantly different at a 95% confidence level (tstat = 0.365 < tcrit = 2.262). This demonstrated that the developed method could be applied for detecting mercury (II) in natural water samples.